2014
DOI: 10.1007/s00464-014-3949-0
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the new generation three-dimensional high definition laparoscopic vision system on surgical skills: a randomized prospective study

Abstract: The majority of the tasks were completed in a shorter time using 3D LVS compared to 2D LVS. The subjective Likert-scale ratings from each group also demonstrated a clear preference for 3D LVS. New 3D LVS has the potential to improve the learning curve, and reduce the operating time and error rate during the performances of laparoscopic surgeons. Our results suggest that the new-generation 3D HD LVS will be helpful for surgeons in laparoscopy (Clinical Trial ID: NCT01799577, Protocol ID: BEHGynobs-4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 29 publications
(59 reference statements)
0
26
0
1
Order By: Relevance
“…In a randomized prospective study by Usta et al, 24 participants were required to perform 10 standardized tasks and asked to report any adverse reactions experienced when using 3D or 2D laparoscopy. There was no difference in visual strain (P=0.087), headache (P=0.134) or facial discomfort (P=0.090) (14). Gómez-Gómez et al measured the mental workload using the NASA Task Load Index with five standardized tasks.…”
Section: Surgeons' Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized prospective study by Usta et al, 24 participants were required to perform 10 standardized tasks and asked to report any adverse reactions experienced when using 3D or 2D laparoscopy. There was no difference in visual strain (P=0.087), headache (P=0.134) or facial discomfort (P=0.090) (14). Gómez-Gómez et al measured the mental workload using the NASA Task Load Index with five standardized tasks.…”
Section: Surgeons' Perspectivementioning
confidence: 99%
“…Headache, nausea and eye strain from 3D laparoscopy have been reported (29)(30)(31)(32), although these were not consistently demonstrated across different studies and subjects (13,14). Three studies reported increased adverse reactions with 3D laparoscopy (25,30,33).…”
Section: Surgeons' Perspectivementioning
confidence: 99%
“…Today, minimally invasive surgery is an established technique in various surgical procedures, and the development in this field continues. In laparoscopy, the original two-dimensional laparoscopic vision system (2D LVS) is being challenged by three-dimensional systems (3D LVS) that provide a stereoscopic perception [1][2][3][4][5]. The advantages reported with 3D vision systems in surgery are shorter operative time, less blood loss, fewer perioperative complications, and shorter length of hospital stay, according to a large meta-analysis performed by Cheng et al [4].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages reported with 3D vision systems in surgery are shorter operative time, less blood loss, fewer perioperative complications, and shorter length of hospital stay, according to a large meta-analysis performed by Cheng et al [4]. In laparoscopic simulation studies, the 3D LVS is proven to be better in terms of shorter task durations, reduced error rates, and a better subjective experience [3,5,6]. However, one major user complaint regarding the 3D LVSs is that it requires shutter glasses, and the system has also been associated with a bad image quality and experiences of headache, dizziness, eyestrain, nausea, and visual disturbance [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation